The relationship between tolerance for uncertainty and academic adjustment: the mediating role of students’ psychological flexibility during COVID-19 - Daşcı, Esma; Salihoğlu, Kübra; Daşcı, Esra (Frontiers in Psychology, 2023)
University students are among the groups most adversely affected by COVID-19 in terms of their psychological and academic well-being, particularly given the pandemic's uncertainty. However, little is known about their psychological flexibility to deal with this uncertain nature of pandemic. This study aimed to examine the mediating role of psychological flexibility (PF) in the relationship between university students' intolerance of uncertainty (IU) and their academic adjustment to the online learning process during COVID-19. Data was collected from 388 university students from Turkey (ages 18 -52 years) who completed five questionnaires -Intolerance of Uncertainty Scale, Acceptance and Action Questionnaire II, Academic Self Efficacy Scale, Educational Stress Scale, and Online Self Regulatory Learning Scale. Additionally, as indicators of students' academic adjustment, perceived academic performance -ranging 1 to 10, and their last academic grade point average before and during the pandemic were also collected. The results indicated that PF and IU had a significant effect on the academic adjustment of students during the pandemic. PF had a complete mediating role between the IU and academic adjustment. Results also revealed that online self-regulation, a sub-dimension of academic adjustment, did not show a significant relationship with any other variable in the model. Research findings showed that psychological flexibility is a very important strength for university students to maintain their academic adjustment in stressful times. The results were discussed in light of the relevant research, and recommendations for further research and implications were provided.